The Mediating Role of Attitudes in the Relationship Between Gender Stereotypes and Preferences for Female Leaders - Amelia Pebi Widi Astuti; Aftina Nurul Husna (Journal of Feminism and Gender Studies, 2026)
Gender stereotypes contribute to the low representation of women in leadership and influence individual preferences in selecting female leaders. These stereotypes, shaped by social constructs, can marginalize women’s roles and reduce trust in female leadership. This study aims to examine the effect of gender stereotypes on the preference for female leaders, with attitudes toward female leadership as a mediating variable. The research was conducted on 152 civil servants in the Semarang City Government using a convenience sampling technique. Data were collected using three instruments: a gender stereotype scale, the Attitudes Toward Women in Leadership scale, and a vignette-based and a vignette-based survey to measure participants’ preference for female leaders. Mediation analysis revealed that female gender stereotypes indirectly influence the preference for female leaders through attitudes toward female leadership, indicating full mediation (β = -0.137, p < 0.05). These findings highlight the importance of fostering more positive attitudes toward female leadership to enhance trust and promote a more equitable and inclusive work environment.